Faktor Minat Anggota terhadap Pembiayaan Syari’ah pada Koperasi Simpan Pinjam dan Pembiayaan Syari’ah Maju Bersama Gondang Pekalongan - Aisyah, Aida; Notoatmojo, M Iqbal (Sekolah Tinggi Agama Islam (STAI) Ki Ageng Pekalongan, Indonesia, 2024)
This research aims to analyze the factors influencing members' interest in sharia financing at the Maju Bersama Gondang Pekalongan Sharia Savings and Loan Cooperative and Financing (KSPPS). In the context of the development of sharia economics in Indonesia, this research identifies several key variables, including promotion, service quality, profit-sharing, and the cooperative's image. The research method used for the analysis is quantitative, with data collection through questionnaires distributed to cooperative members. The research results show that all these factors have a significant influence on members' interest in using sharia financing products. This study contributes to the importance of effective cooperative marketing strategies and increasing member satisfaction, as well as contributing to the development of sharia cooperatives in Indonesia.